A fantázia határtalan – számvitel diákszemmel - Szarvas-Fekete, Tibor; Ágoston, Anita; Wickert, Irén (Acta Scientiarum Socialium, 2019)
"A talent is someone who knows more than they had learned", quoted the jury of the „Dal 2017” in the finals, after we saw the great performance of a 17 year old boy. What skills do the students of Kaposvár University have? How much part of their performance during the exams is knowledge and how much is fantasy? Adopting Henry Ford’s witticism we can expect that smart, diligent students will do themselves justice and get good grades; the lazy and less talented students will vegetate whereas the hard-working but untalented students will fall out of the sieve. However, what about smart, but lazy students? Those who "forget" to learn but due to their powerful imagination, can create something unbelievable during the exam, overcoming the greatest cruxes in the good sense. This article deals with this theory in humorous form: what the accounting is like with the eyes of a clever, creative but lazy student.
Keywords: accounting; students; examining; creativity